Contribution of Physical Fitness, Socio-Economic Conditions and School Environment towards Academic Learning Achievement of Elementary School Students in North Semarang District 2019 - Rosyada, Moh. Rizal Fahmi; Sulaiman, Sulaiman; Rustiadi, Tri (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
The purpose of this study is to find out and analyze: 1) The contribution of physical fitness towards learning achievement, 2) The contribution of socio-economic conditions towards learning achievement, 3) The contribution of the school environment towards learning achievement, 4) The contribution of physical fitness and socio-economic conditions towards learning achievement, 5) The contribution of socio-economic conditions and school environment towards learning achievement, 6) The contribution of physical fitness and school environment towards learning achievement, and 7) The contribution of physical fitness, socio-economic conditions and the school environment towards learning achievement. This research is a quantitative study. The population is 393 students and 13 elementary schools. Data analysis techniques using multiple correlation analysis with Slovin formula. The results of the study revealed: 1) Contribution of physical fitness towards learning achievement is moderate with 43%, 2) Contribution of socio-economic conditions towards learning achievement is low with 43%, 3) Contribution of school environment towards learning achievement has incomplete criteria with 65%, 4) Contribution of physical fitness and socio-economic conditions towards learning achievement is 25%, 5) Contribution of physical fitness and school environment towards learning achievement is 67.5%, 6) Contribution of socio-economic conditions and school environment towards learning achievement is 67.5%, and 7) Contribution of physical fitness, socio-economic conditions and school environment towards academic learning achievement is 40%.